Ethylene: A Natural Regulator of Sex Expression of Cucumis melo L - Byers, R. E. (1972)
Sex expression in cucumber (Cucumis sativus L.) and muskmelon (C. melo L.) was correlated with endogenous ethylene production. Plants of gynoecious (all female) sex types of the two species produced more ethylene than monoecius (male-female) plants. C. melo plants of a gynoecious sex type that normally produce only pistillate (female) flowers, when grown with hypobaric ventilation to facilitate removal of endogenous gases by diffusion, produced perfect (hermaphroditic) flowers. When either the plant was returned to atmospheric pressure or when the reduced-pressure ventilating stream was supplemented with ethylene, the same plants produced pistillate flowers. Enrichment of the atmosphere at either normal or reduced pressure with CO(2), a competitive inhibitor of ethylene action, also resulted in development of perfect flowers. Foliar application of a benzothiadiazole, a postulated inhibitor of ethylene action, resulted in formation of perfect flowers on gynoecious plants of C. melo and of staminate (male) flowers on gynoecious C. sativus. Based on these findings, it is proposed that ethylene is an endogenous regulator of sex expression in C. sativus and C. melo.